2020
DOI: 10.1038/s41598-019-57349-z
|View full text |Cite
|
Sign up to set email alerts
|

A Place-based Assessment of Flash Flood Hazard and Vulnerability in the Contiguous United States

Abstract: Flash flood is among the most catastrophic natural hazards which causes disruption in the environment and societies. Flash flood is mainly initiated by intense rainfall, and due to its rapid onset (within six hours of rainfall), taking action for effective response is challenging. Building resilience to flash floods require understanding of the socio-economic characteristics of the societies and their vulnerability to these extreme events. This study provides a comprehensive assessment of socio-economic vulner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 60 publications
1
44
0
1
Order By: Relevance
“…Social vulnerability results when social, political, and economic processes combine to produce heightened susceptibility to hazards for some populations [13][14][15][16]. The application of the concept can be found in health research, hazard mitigation planning, and environmental social sciences, but the use and selection of indicators can significantly vary [9,12,15,17,18].…”
Section: Social Vulnerabilitymentioning
confidence: 99%
“…Social vulnerability results when social, political, and economic processes combine to produce heightened susceptibility to hazards for some populations [13][14][15][16]. The application of the concept can be found in health research, hazard mitigation planning, and environmental social sciences, but the use and selection of indicators can significantly vary [9,12,15,17,18].…”
Section: Social Vulnerabilitymentioning
confidence: 99%
“…Based on the Multicollinearity study and estimation of predictive power and information gain method, the study of Costache et al revealed that the Multilayer Perceptron Statistical Index integration has the highest efficiency and is applied to the actual region mapping (Costache et al, 2020). The socio-economic vulnerability of flash floods was comprehensively assessed by Khajehei et al, and the main characteristics of flash floods, such as frequency, duration, severity, and magnitude, were investigated (Khajehei et al, 2020). Sezen et al describe the process of developing computational risk assessment methods that incorporate the risks associated with earthquake and flood events into the traditional probabilistic risk assessment (Sezen et al, 2019) (Banda, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ahmadalipour and Moradkhani (2019) investigated the spatiotemporal characteristics of flash flooding hazard over the Contiguous United States (CONUS). Also, Khajehei et al (2020) assessed the socioeconomic vulnerability of flash flooding at the county scale across the entire CONUS while accounting for flash flood characteristics including duration, frequency, magnitude and severity.…”
Section: Introductionmentioning
confidence: 99%